(untitled) (Journal of Cancer Research Updates, 2013)
According to the AML-BFM 2004 Interim, a treatment protocol used in Poland since 2005, presence of FLT3 internal tandem duplication (FLT3/ITD) qualifies a patient with acute myeloid leukemia (AML) to a high-risk group (HRG). The present study was aimed to identify the prevalence of FLT3/ITD in children with AML in Poland and to evaluate its prognostic significance in the HRG patients. Out of 291 children with de novo AML treated in 14 Polish centers between January 2006 and December 2012, samples from 174 patients were available for FLT3/ITD analysis. Among study patients 108 children (61.7%) were qualified to HRG. Genomic DNA samples from bone marrow were tested for identification of FLT3/ITD mutation by PCR amplification of exon 14 and 15 of FLT3 gene. Clinical features and treatment outcome in patients with and without FLT3/ITD were analyzed in the study. The FLT3/ITD was found in 14 (12.9%) of 108 HRG children. There were no significant differences between children with and without FLT3/ITD in age and FAB distribution. The white blood cells count in peripheral blood at diagnosis was significantly higher (p <0.01) in the children with FLT3/ITD. Over 5-year overall survival rate for FLT3/ITD positive children was worse (42.4%) comparing to FLT3/ITD negative children (58.9%), but the statistical difference was not significant. However, over 5-year survivals free from treatment failures were similar. The FLT3/ITD rate (12.9%) observed in the study corresponded to the published data. There was no significant impact of FLT3/ITD mutation on survival rates, although further studies are needed on this subject.